Organised retailing and agri-business - Rao, N. Chandrasekhara; Rao, N. Chandrasekhara; Radhakrishna, R.; Mishra, Ram Kumar; Kata, Venkata Reddy (New Delhi Springer, 2016)
This book examines the performance of organized retail chains supplying the agri-input and output services in terms of achieving their objective of utilising collective bargaining power in the marketing of their agricultural produce, integrating empirical experience from India and other selected developing countries. The scenario of marketing for agricultural products has been undergoing rapid changes with the rise of organised retailing.